Hypnerotomachia Polifili's Porta Magna reconsidered: the antique model and the dream of a lost city - Gudelj, Jasenka (Array, 2011)
The love novel Hypnerotomachia Polifili (1499), remains one of the most influential and enigmatic books of the Italian Renaissance. Because of its numerous references to classical architecture and interesting illustrations representing all'antica buildings, there is a tendency to see Hypnerotomachia as a pseudo-architectural treatise. The paper analyses the famous passage of the novel describing the Porta Magna comparing its architectural elements, decoration and proportional system to the Arch of the Sergi in Pula, establishing for the first time its relationship with an existing antique model. The accompanying illustration indicates a slightly different set of references, all ultimately related to the same antique model. The heirs of the Sergi, expelled from Pula in the 14th century, in the 15th century experience new fortune in Treviso. Thus, the reference to the Arch of Sergi also permits a proposition to read the novel as a dream of a lost city.